2017
DOI: 10.15666/aeer/1503_12791291
|View full text |Cite
|
Sign up to set email alerts
|

Determination of some botanical, phenological, physical and chemical characteristics of walnut (Juglans regia L.) genotypes grown in Tureky

Abstract: Abstract. Botanical, phenological, physical and chemical characteristics of promising walnut (Juglans regia L.) genotypes grown in the Beyazsu region (Mardin) of Turkey were studied during years 2012-2013. The physical properties of genotypes were attributed to the quality criteria of nuts. Fruit weight (Fw1), kernel weight (Kw), fruit length (Fl), fruit witdh (Fw2), fruit height (Fh), kerrnel ratio (Kr) and shell thickness (St) were determined as 9. 67-15.68 g, 5.35-8.54 g, 5.35-8.54 g, 33.53-45.78 mm, 28.42-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Numerous studies have been conducted on walnut fruits concerning biochemical, phytochemical, and antioxidant characteristics, and their contribution to human health and nutrition. Walnut kernel has a high amount of protein, fat, vitamins, minerals, and polyphenols, therefore, placing walnut in the human diet is inevitable [3,4]. Walnut has been also using in folk medicine due to its high antioxidant capacity [5] and alkaloids content with antimicrobial properties and ω-3 fatty acid concentration [6] for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted on walnut fruits concerning biochemical, phytochemical, and antioxidant characteristics, and their contribution to human health and nutrition. Walnut kernel has a high amount of protein, fat, vitamins, minerals, and polyphenols, therefore, placing walnut in the human diet is inevitable [3,4]. Walnut has been also using in folk medicine due to its high antioxidant capacity [5] and alkaloids content with antimicrobial properties and ω-3 fatty acid concentration [6] for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from 12YE28 and 12YE29, the genotypes had total oil content of over 50%. Simsek et al [13] reported a higher total oil content of 63.63-66.78% for 12 promising genotypes in Bingol but in different districts. However, the average total oil content of the genotypes of the present study was ca.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, there is a wide genetic variation adapted to the ecological conditions of the region and having different characteristics from each other. There is only a little literature related to walnuts grown in the Bingol province [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The reference standard cultivars such as Payne (phenologically early season variety), Hartley (phenologically midseason variety), Franquette (phenologically late season variety) or local check variety are frequently used to compare and characterize germplasm for phenological characters as these characters show high variability due to changes in agroclimatic conditions of the cultivation area (McGranahan and Forde 1985). The phenological characteristics of walnut genotypes and cultivars can vary with harvest year, environmental conditions, horticultural practices, and genetic characteristics, altitude, planting direction, plant age (Simsek et al, 2017, Akca et al, 2009Sutyemez et al, 2018). The phenological characters bud break and leafing date terms are used interchangeably but leafing date is the date when one of the leaves unfolds and occours few days after bud break.…”
Section: Phenological Characteristicsmentioning
confidence: 99%